The Influence of Brand Reputation, Brand Equity, and Brand Satisfaction on Brand Loyalty of Mie Gacoan - Saputra, Aldo Hernanda; Setiawan, Budi; Cahyani, Putri Dwi (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
The development and competition of culinary businesses in Indonesia are increasingly competitive. This study was conducted to analyze the influence of brand reputation, brand equity, and brand satisfaction on brand loyalty of Mie Gacoan. This quantitative research method collected data by distributing questionnaires to a sample of 180 respondents who had purchased Mie Gacoan products. The reliability of the instrument was assessed through validity and reliability tests, while the data analysis method used path analysis with the help of the SmartPLS version 3.0. The results proved that brand reputation did not affect brand loyalty, but had a positive and significant effect on both brand equity and brand satisfaction. Meanwhile, the results of this study also proved that brand equity and brand satisfaction have a positive and significant influence on brand loyalty in the Mie Gacoan culinary industry.